A comparative study of two nanosubstrates for the on-line solid phase extraction of antimony by FI-HG-AAS - Londonio, Juan Agustín; Parodi, Belén; Gil, Raul Andres; Alshehri, Saad M.; Yamauchi, Yusuke; Smichowski, Patricia Nora (Elsevier Science, 2016)
Fil: Londonio, Juan Agustín. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín; Argentina